THE EFFECT OF MURĀBAHAH AND MUSYĀRAKAH FINANCING DISTRIBUTION ON OPERATIONAL REVENUE OF PEOPLE'S FINANCING BANK SHARIA 2015-2018 - yakinah yakinah; kamaluddin ritonga; arti damisa; sulaiman efendi (Journal Of Sharia Banking, 2020)
This research aimed to determine the effect of Murābahah and Musyārakah financing distribution on operating income. This research use the reporting finance by the financial fervices authority of people’s finance Bank Syariah in 2015-2018 as a sample. It used double linear regression method. The result shows that Murābahah and Musyārakah finance have a positive influence on operating income.Abdurrahmat Fhatoni, Metodologi Penelitian Teknik Penyusunan Skripsi, Jakarta: Rineka Cipta, 2011. Adiwarman Karim, Bank Islam: Analisis Fiqih dan Keuangan, Jakarta: PT Raja Grafindo Persada, 2011. Agus Irianto, Statistik Konsep Dasar Aplikasi, dan Pengembangannya, Jakarta: Kencana Prenada Media Group, 2009. Ascarya, Akad dan Produk Bank Syariah, Jakarta: Rajawali Pers, 2013. Departemen Agama, Al-Qur’an dan Terjemahanya, Semarang: Toha Putra, 2010. Duwi Priyatno, SPSS 22 Pengolahan Data Terpraktis, Yogyakarta: CV. Andi Offset, 2014.Dwi Suwiknyo, Kompilasi Tafsir Ayat-Ayat Ekonomi Islam, Yogyakarta: Pustaka Pelajar, 2010. Herman Darmawi, Manajemen Perbankan, Jakarta: Bumi Aksara, 2012. Herry Sutanto Khaerul Umam, Manajemen Pemasaran Bank Syariah, Bandung: Pustaka Setia, 2013. Husein Umar, Metode Penelitian untuk Skripsi dan Tesis Bisnis. Jakarta: Rajawali Pers, 2013. Imam Ghozali, Aplikasi Analisis Multivariate dengan Program IBM SPSS 21, Semarang: Universitas Diponegoro, 2013. Iqbal Hasan, Analisis Data Penelitian Dengan Statistik, Jakarta: PT. Bumi Akasara, 2004. Ismail, Perbankan Syariah, Jakarta: Kencana, 2011. Mardani, Fiqh Ekonomi Syariah, Jakarta: Kencana, 2012. Maulana Hasanuddin Jaih Mubarok, Perkembangan Akad Musyarakah, Jakarta: Kencana, 2012. Mudrajat Kuncoro, Metode Riset untuk Bisnis dan Ekonomi, Jakarta:      Erlangga, 2009. M. Nur Rianto Al-Arif, Lembaga Keuangan Syariah, Bandung:                    Pustaka Setia, 2012. Muhammad Syafi’i Antonio, Bank Syariah: Dari Teori ke Praktik, Jakarta: Gema Insani Pers, 2016. Muhammad Teguh, Metodologi penelitian ekonomi Teori dan Aplikasi, Jakarta: PT Raja Grafindo Persada, 2005. Rizal Yaya, dkk., Akuntansi Perbankan Syariah, Jakarta: Selemba Empat, 2014. Singgih Santoso, Panduan Lengkap SPSS Versi 23, Jakarta: Alex Media Komputindo, 2016. Slamet Haryono, Analisis Laporan Keuangan Perbankan Syariah, Yogyakarta: Pustaka Sayid Sabiq, 2009. Sugiyono, Metode Penelitian Bisnis (Bandung: Alfabeta, 2012), hlm. 88. Sutan Remy Sjahdeini, Perbankan Syariah Produk-Produk dan Aspek-Aspek Hukumnya, Jakarta: Kencana Prenada Media Group, 2014. Trisadini P.Usanti dan Abd Shomad, Transaksi Bank Syariah, Jakarta: Bumi Aksara, 2013. Veithzal Rivai Arvian Arifin, Islamic Banking, Jakarta: PT.Bumi Aksara, 2010. Wiroso, Produk Perbankan Syariah, Jakarta: LPFE Usakti, 2009. Zainul Arifin, Dasar-Dasar Manajemen Bank Syariah, Jakarta: AlvaBet, 2002.